Influência da queima e aditivos químicos e bacterianos na composição química de silagens de cana-de-açúcar - Siqueira, G. R. [UNESP]; Reis, R. A. [UNESP]; Schocken-Iturrino, R. P. [UNESP]; Bernardes, T. F. [UNESP]; Pires, A. J. V.; Roth, M. T. P. [UNESP]; Amaral, R. C. [UNESP] (SciELO Espana/Repisalud, 2009)
The objective of this trial was to evaluate the effect of the chemical (urea, sodium benzoate, and sodium hydroxide) and microbiological (Propionibacterium acidipropionici + Lactobacillus plantarum, and Lactobacillus buchneri) additives on the sugarcane nutritive value, ensiled crude or after burned, using a factorial scheme 2 (burned or crude sugar cane) x 6 (five additives urea, sodium benzoate, sodium hydroxide, Propionibacterium acidipropionici + Lactobacillus plantarum, and Lactobacillus buchneri plus control). It was evaluated the sugar cane chemical composition, before and after ensilage. The sugar cane NDF contents increased (51.3%, before ensilage) to 67.8% after fermentation period. The highest true digestible dry matter recovery values, 83.6 and 79.8% were observed on the burned sugar cane silage treated with NaOH or L. buchneri, respectively. The NaOH, and L. buchneri showed more efficiency in reducing nutritive looses during the fermentation phase of the crude or burned sugar cane silage.
Effect of the burn chemical and bacterial additives on the sugarcane silage chemical composition
Keywords: Additives; Fermentation; Inoculants; Silage; Animalia; Bacteria (microorganisms); Lactobacillus; Lactobacillus buchneri; Lactobacillus plantarum; Propionibacterium; Propionibacterium acidipropionici; Saccharum